Neuronal expression of human immunodeficiency virus type 1 env proteins in transgenic mice: distribution in the central nervous system and pathological alterations. - Berrada, F (1995)
It is now well documented that human immunodeficiency virus type 1 (HIV-1) induces encephalopathy in patients with AIDS. In vitro studies have implicated the envelope protein (gp120) as a factor which causes neuronal death. To better evaluate the role and elucidate the mechanisms of gp120 neurotoxicity, we have developed transgenic mice carrying a segment of the HIV-1 genome that expresses the viral gp160 protein under the control of the human neurofilament light gene promoter. In two separate lines of transgenic mice, the Env protein was found to be expressed in several nuclei of the brain stem and in the anterior horns of the spinal cord. The two lines showed identical patterns of Env expression. Neuropathological evaluation revealed numerous abnormal dendritic swellings in the immunostained motor neuron structures. Large and numerous neuritic swellings were also prominent in the nucleus gracilis and in the gracilis and cuneate fascicles. In addition, reactive astrocytosis was observed in several immunoreactive areas of the central nervous system. These transgenic mice offer a unique model to further investigate the role of HIV-1 Env protein in neuronal toxicity and to help elucidate the mechanisms that are involved.